1983
DOI: 10.1083/jcb.96.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans in primate arteries. III. Characterization of the proteoglycans synthesized by arterial smooth muscle cells in culture.

Abstract: Near confluent monolayers of arterial smooth muscle cells derived from Macaca nemestrina were labeled with Na2[aSS]O4 and the newly synthesized proteoglycans present in the culture medium and cell layer were extracted with either 4 M guanidine HCI (dissociative solvent) or 0.5 M guanidine HCI (associative solvent) in the presence of protease inhibitors. The proteoglycans in both compartments were further purified by cesium chloride density gradient ultracentrifugation. Two size classes of proteoglycans were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…The gel shown is representative of seven independent experiments. C, control; T, troglitazone; R, rosiglitazone (containing predominantly biglycan and versican) [14,25] proteoglycans synthesised in the presence of troglitazone were smaller than proteoglycans synthesised by control cells (peak 1, K av 0.35±0.05 vs 0.39±0.04, n=6, p=0.04; peak 2 K av 0.69±0.01 vs 0.71±0.009, n=6, p=0.05, in the absence and presence of troglitazone respectively; Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gel shown is representative of seven independent experiments. C, control; T, troglitazone; R, rosiglitazone (containing predominantly biglycan and versican) [14,25] proteoglycans synthesised in the presence of troglitazone were smaller than proteoglycans synthesised by control cells (peak 1, K av 0.35±0.05 vs 0.39±0.04, n=6, p=0.04; peak 2 K av 0.69±0.01 vs 0.71±0.009, n=6, p=0.05, in the absence and presence of troglitazone respectively; Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Secreted proteoglycans from the different experiments were concentrated and purified using separate diethylaminoethyl-sephacel mini-columns [20,22]. Proteoglycans were separated into large (peak 1, containing predominantly the chondroitin sulphate proteoglycan, versican [20,23]) and small (peak 2, containing a mixture of dermatan sulphate proteoglycans, biglycan and decorin [24]) size classes using size exclusion chromatography [14,25]. Glycosaminoglycan chains were released from core proteins as described previously [20].…”
Section: Methodsmentioning
confidence: 99%
“…Prior to chromatography, one of the two aliquots was digested with 2 units of Streptomyces hyaluronidase (Sigma) at 37°C for 24 h. Under associative conditions, proteoglycans containing aggregates will elute in the void volume. Digestion of components of the aggregate, for example by hyaluronidase, will shift the elution position of the proteoglycans to a later fraction (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…Strain Increases Proteoglycan Aggregation-To determine whether increased synthesis of versican was accompanied by increased formation of high molecular weight versican-hyaluronan aggregates, we examined the presence of native aggregates using size exclusion chromatography under associative conditions (34,35). The absence of material at the void volume of a Sepharose CL-2B molecular sieve column under associative conditions in the control medium proteoglycans indicated that no aggregate formed (Fig.…”
Section: Fig 2 Strain Increases the Accumulation Of Proteoglycans Bmentioning
confidence: 99%
“…Biochemical studies and characterization of PGs found in the aorta (12)(13)(14) and in cultures of arterial muscle cells (15,16) have demonstrated that the main PG synthesized is versican, a chondroitin sulfate PG. Recently, a transmembrane PG was described for smooth muscle cells from mouse aorta (17).…”
Section: Introductionmentioning
confidence: 99%